Effect of steps and gaps on aerothermodynamics for the IXV hypersonic vehicle. (24th September 2012) - Sourgen, Frédéric; Fontaine, Joëlle; Garçon, François; Verant, J-L.; Pelissier, C.; Tribot, Jean-Pierre; Hauwaert, Pierre Van; Spel, Martin; Vos, Jan
The general aerothermodynamics environment of hypersonic vehicles is usually performed considering a smooth simplified geometry. However, in the case of the intermediate experimental vehicle (IXV), the thermal protection system includes a mono-block ceramic matrix composite nose and an assembly of shingles between which steps and gaps are generated. From an aerothermodynamic point of view, such a distributed roughness layout cannot be ignored in terms of modification of the interaction between the flow and the body and possible induced transition along the windward side. To assess these effects, dedicated wind tunnel tests and numerical simulations have been performed. This paper presents the general logic of the work, with emphasis on the wind tunnel model design, tests involving infrared thermal measurements as well as the computational fluid dynamics (CFD) rebuilding of the flow in the wind tunnel and the extrapolation from ground to flight.